Pengaruh Metode Tsaqifa dan Motivasi Menghafal Al-Qur’an Terhadap kualitas Hafalan Al-Qur’an Santriwati Ma’had Maryam Kota Depok - Welasari; Syahril (Educational Research Indonesia, 2025)
The urgency of this research is important because memorizing the Quran is a form of worship to Allah SWT and provides many benefits including serving as a guide in life and maintaining originality towards the Quran. In memorizing the Quran, good motivation and the correct method must be included. This is essential to preserve the originality of the Quran from generation to generation as it should be known. There are problems in memorizing it. Many who study for years still do not complete their memorization of the Quran, the quality of memorization is not perfect, and there are still errors in pronunciation. To make the Quran easy to memorize, this relates to the methods used and the motivation in memorizing the Quran. The methods used for memorization will obviously vary, as will the motivation for memorizing the Quran. One method of learning the Quran is tsaqifa.Therefore, the purpose of this research is to analyze the extent of the influence of the Tsaqifa method and motivation in memorizing the Qur'an on the quality of the Qur'anic memorization of female students at Ta'limil Qur'an Ma'had Maryam in Depok City. This research uses a quantitative method, with data collection techniques conducted through observation, questionnaires, and tests. The processing and statistical analysis of the data were performed using SPSS 21, with the subject of the research being the female students at Ta'limil Qur'an Ma'had Maryam in Depok City. The theories used are the Tsaqifa method, motivation for memorizing the Qur'an (pure motivation), and the quality of Qur'anic memorization.Therefore, the purpose of this research is to analyze the extent of the influence of the Tsaqifa method and motivation in memorizing the Qur'an on the quality of the Qur'anic memorization of female students at Ta'limil Qur'an Ma'had Maryam in Depok City. This research uses a quantitative method, with data collection techniques conducted through observation, questionnaires, and tests. The processing and statistical analysis of the data were performed using SPSS 21, with the subject of the research being the female students at Ta'limil Qur'an Ma'had Maryam in Depok City. The theories used are the Tsaqifa method, motivation for memorizing the Qur'an (pure motivation), and the quality of Qur'anic memorization.